Respuesta :
x + 2y = 8
x + 3y = 12
solve for x;
x + 2y = 8
x = 8 - 2y
substitute to find the y;
8 - 2y + 3y = 12
8 + y = 12
y = 12 - 8
y = 4
solve for x, given y;
x = 8 - 2y
x = 8 - 2(4)
x = 8 - 8
x = 0
(0, 4) << your answer
hope this helps, God bless!
x + 3y = 12
solve for x;
x + 2y = 8
x = 8 - 2y
substitute to find the y;
8 - 2y + 3y = 12
8 + y = 12
y = 12 - 8
y = 4
solve for x, given y;
x = 8 - 2y
x = 8 - 2(4)
x = 8 - 8
x = 0
(0, 4) << your answer
hope this helps, God bless!
Given system of equations :
x + 2y = 8
x + 3y = 12
From above two equations :
x = 8 - 2y
x = 12 - 3y
Equating both of them
8 - 2y = 12 - 3y
12 - 3y = 8 - 2y
12 - 8 = 3y - 2y = y
4 = y
Hence , substitute the respective value : in any of the raw equations :
x + 2y = 8
x + 2 ( 4 ) = 8
x + 8 = 8
Hence , x = 0 ; y = 4
x + 2y = 8
x + 3y = 12
From above two equations :
x = 8 - 2y
x = 12 - 3y
Equating both of them
8 - 2y = 12 - 3y
12 - 3y = 8 - 2y
12 - 8 = 3y - 2y = y
4 = y
Hence , substitute the respective value : in any of the raw equations :
x + 2y = 8
x + 2 ( 4 ) = 8
x + 8 = 8
Hence , x = 0 ; y = 4